LEXICAL COLLOCATIONAL ERRORS MADE BY EFL HIGH SCHOOL STUDENTS - Ahmed, Rezheen; Mohammed , Fakhir (Humanities Journal of University of Zakho, 2024)
This research paper addresses various lexical collocational errors made by EFL private school students, aiming to investigate their writings (essays and paragraphs) through detailed analysis. The primary objectives of this study are to identify various lexical collocation errors in the written compositions of students at the school level and to provide the correct forms of these lexical collocations to enhance their writing accuracy. The study utilizes both qualitative and quantitative methods, focusing on a sample of 50 randomly selected students (males and females), who participated voluntarily. By using qualitative and quantitative methods and adopting the classification of lexical collocational errors by Benson et al. (1997), for data analysis and to check the acceptance of word combinations, these errors were manually identified in the target written tasks. Then, the researchers used the HASK collocation database (www.pelcra.pl/hask_en/), a reliable online resource containing a large number of collocations. The extracted errors were analyzed and interpreted, with their frequencies and percentages tabulated using Excel bar charts. The findings of the study conclude that EFL students make diverse errors in using lexical collocations in their writing when they try to express their thoughts and ideas. In the analysis of 50 academic pieces of writing, 58 lexical collocation errors were found. It was also found that two specific patterns, (verb + noun) and (verb + adverb) were rarely or almost never used by the participants of the study. The study also found that literal translation from the native language to the target language and limited knowledge of collocations were the main reasons behind these errors. The current study is valuable since collocations play an essential role in improving writing skills. Particularly, the identification of common lexical collocation errors helps educators target specific instructional areas and understand their impact on students' long-term language development. The findings also aid curriculum developers in addressing lexical challenges faced by EFL high school students.